2013
DOI: 10.1093/ndt/gfs548
|View full text |Cite
|
Sign up to set email alerts
|

Use of sodium thiosulphate in a multi-interventional setting for the treatment of calciphylaxis in dialysis patients

Abstract: Calciphylaxis remains a serious complication with high mortality. Early and consistent therapy including STS may help to improve the disease outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
77
0
9

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(90 citation statements)
references
References 35 publications
4
77
0
9
Order By: Relevance
“…Patients can present with hemorrhagic vesicles/bullae that precede the progression to necrosis and commonly develop painful, irregularly shaped, nonhealing ulcers. Lesion distribution, specifically proximal lesions (lesions on the trunk, thighs, and upper arms) versus distal lesions (lesions on the calves and forearms), does not seem to be a clear prognostic indicator as previously thought (69,74,80). Systemic symptoms secondary to vascular and extravascular calcification of internal organs and soft tissues may also occur.…”
Section: Metastatic Calcificationmentioning
confidence: 75%
See 1 more Smart Citation
“…Patients can present with hemorrhagic vesicles/bullae that precede the progression to necrosis and commonly develop painful, irregularly shaped, nonhealing ulcers. Lesion distribution, specifically proximal lesions (lesions on the trunk, thighs, and upper arms) versus distal lesions (lesions on the calves and forearms), does not seem to be a clear prognostic indicator as previously thought (69,74,80). Systemic symptoms secondary to vascular and extravascular calcification of internal organs and soft tissues may also occur.…”
Section: Metastatic Calcificationmentioning
confidence: 75%
“…CKD/ESRD, dialysis therapy, and commonly occurring comorbid conditions, like hypertension, hypercholesterolemia, obesity, and diabetes mellitus, increase oxidative stress (69,74,76,80). Vascular calcification is promoted in the presence of increased oxidative stress by reactive oxygen species that also leads to a state of systemic inflammation, which is evidenced by increased levels of TNF-a, IL-1, and IL-6 (76).…”
Section: Metastatic Calcificationmentioning
confidence: 99%
“…The effect of sodium thiosulfate has been reported to rapidly bring relief from severe pain within days to weeks and to heal skin ulcerations within weeks to months [6,9]. The adverse effects of intravenous sodium thiosulfate can be obstacles.…”
Section: Discussionmentioning
confidence: 99%
“…It is not possible to distinguish which cases may be sensitive to sodium thiosulfate. A retrospective study [9] showed that a delay in diagnosis and treatment, or the complications of diabetes, coronary artery disease, peripheral artery disease, or heart failure was associated with poor prognosis. In this case, we speculated that the complications of diabetes and ASO with APS were one of the reasons for the ineffectiveness of sodium thiosulfate.…”
Section: Discussionmentioning
confidence: 99%
“…In zwei unkontrollierten Fallserien mit Kalziphylaxiepatienten aus Österreich (n = 27) [25] und aus den USA (n = 172) [16] …”
unclassified